Adsorption material for enrichment and extraction of benzimidazole drugs as well as preparation method and use method of adsorption material
By developing the porous material BTT-Py and constructing the magnetic adsorption material Fe3O4@SiO2@BTT-Py, the problem of rapid and efficient enrichment of various benzimidazole drugs in water samples in the prior art is solved, and the simultaneous extraction and stable and repeatable detection effect of 19 drugs is achieved.
Patent Information
- Application Number
- CN202411739714.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art is difficult to quickly and efficiently extract a variety of benzimidazole drugs from water samples, and there is a potential threat to the environment and human health.
A porous material BTT-Py was developed, which was produced by reaction of 1,3,5-benzenetrithiophenol, pyrrole and paraformaldehyde under hydrochloric acid catalyzed action. The material has a large specific surface area, a variety of action forces (such as hydrogen bonding, π-π conjugation) and magnetic properties, and is used to construct the magnetic adsorption material Fe3O4@SiO2@BTT-Py.
The simultaneous enrichment and extraction of 19 benzimidazole drugs has been achieved, which improves detection accuracy and efficiency, and the material is stable and reusable, which is suitable for the rapid separation and analysis of various drugs in water samples.
Smart Images

Figure CN119549129A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of enrichment, extraction and separation of residual drugs in the environment, and in particular to an adsorption material for enrichment and extraction of benzimidazole drugs, as well as the preparation and application of the adsorption material. Background Art
[0002] Benzimidazoles have a broad spectrum of biological activities due to their structural specificity, such as antiparasitic, antiviral, antibacterial, anticancer and antihypertensive. They play an important role in the field of pharmaceutical chemistry and are widely used in the fields of medicine and pesticides. After being taken by humans or animals, part of the benzimidazoles is absorbed by the human or animal body, and the rest is excreted into the environment through urine. With the widespread, long-term, frequent and improper use of drugs, drug residues accumulate in environmental water bodies and gradually show harmfulness, such as toxic effects on aquatic organisms, inhibition of the activity of probiotics, and even blocking the circulation of the ecosystem; they may also enter the human body through drinking water or the food chain, causing allergic reactions, diarrhea, hematopoietic dysfunction and other diseases, and even causing certain harm to the human urinary system and thyroid gland. Severe cases can cause necrotizing lymphadenopathy, pulmonary edema, induce thyroid cancer, and may also cause congenital malformations of the fetus. Therefore, some countries and organizations have set maximum residue limits (MRLs) for benzimidazoles, so it is very important to accurately detect the residues of benzimidazoles in the water environment.
[0003] Common methods for detecting benzimidazole drug residues include ultraviolet detection (UV), fluorescence detection (FLD) and liquid chromatography tandem mass spectrometry (LC-MS / MS). The premise of influencing the accuracy of detection is the effective pretreatment of the sample to be tested, because the concentration of drug residues in environmental water samples is often lower than the detection limit of various detection methods, and there are many interferences, which makes it difficult to meet the requirements of direct detection. It is necessary to enrich and extract the benzimidazole drugs in the water sample before detection. Although there are many sample pretreatment technologies for benzimidazole drugs, such as liquid-liquid extraction (LLE) and solid phase extraction (SPE), these methods have their own limitations. LLE consumes a large amount of organic solvents, which will cause harm to the environment and human health; SPE has problems such as less types of effectively enriched benzimidazole drugs. If a new adsorbent material can be developed to quickly and efficiently extract a variety of benzimidazole drugs in water, it will have broad application prospects in the fields of environmental protection and water quality monitoring. Summary of the invention
[0004] In order to solve the shortcomings of the prior art, the present invention provides an adsorption material for the enrichment and extraction of benzimidazole drugs. The adsorption material can form multiple forces with the target compound to achieve the separation advantage of simultaneously extracting 19 benzimidazole drugs. The adsorption material is made into a magnetic adsorption material, which has the advantages of simple preparation process, large specific surface area, strong magnetism, stable structure and reusability, and can meet the needs of rapid separation and analysis of multiple benzimidazole drugs in water samples.
[0005] To achieve the above-mentioned purpose, the present invention provides an adsorption material for enriching and extracting benzimidazole drugs, which has a porous material BTT-Py that can enrich benzimidazole drugs. The porous material BTT-Py is prepared by reacting 1,3,5-benzenetrithiol, pyrrole and polyformaldehyde under the catalysis of hydrochloric acid.
[0006] The present invention obtains a porous material BTT-Py having a rich structure of benzene rings, sulfur atoms and nitrogen atoms by reacting 1,3,5-benzenetrithiol, pyrrole and polyformaldehyde under the catalysis of hydrochloric acid. It is easy to form various forces with benzimidazole substances, such as intermolecular hydrogen bonds, π-π conjugation, etc., and the material has a large specific surface area and porosity, thereby realizing efficient enrichment and extraction of benzimidazole drugs, and achieving the advantage of extracting 19 benzimidazole drugs at the same time. In addition, the adsorption material has strong stability and can be reused, meeting the needs of rapid enrichment, extraction, separation and analysis of multiple benzimidazole drugs in the sample to be tested.
[0007] As a limitation of the above technical solution, the porous material BTT-Py is prepared by placing 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid in a solvent 1,4-dioxane and heating the mixture at 90±5°C for reaction.
[0008] Using 1,3,5-benzenetrithiol, pyrrole and polyformaldehyde as raw materials, providing benzene rings with conjugated structures and abundant sulfur atoms, nitrogen atoms and other reaction sites, using 1,4-dioxane as the reaction solvent and hydrochloric acid as the catalyst, a condensation reaction occurs at a temperature of 90±5°C. The process is relatively simple and easy to control, and does not need to be carried out under vacuum conditions. The obtained material is stable and conducive to repeated use.
[0009] As a limitation of the above technical solution, the adsorption material is an adsorption resin or a magnetic adsorption material.
[0010] The porous material BTT-Py is made into an adsorption resin or a magnetic adsorption material, which facilitates the enrichment and extraction of benzimidazole drugs, improves the enrichment and extraction rate, and optimizes the subsequent separation and detection results.
[0011] As a limitation of the above technical solution, the magnetic adsorption material has a core-shell structure, with magnetic Fe3O4 nanoparticles as the core and porous material BTT-Py as the shell.
[0012] As a limitation of the above technical solution, the magnetic adsorption material is formed by firstly wrapping SiO2 on the surface of magnetic Fe3O4 nanoparticles to form Fe3O4@SiO2 particles, and then being wrapped by the porous material BTT-Py.
[0013] Specifically, the preparation of the magnetic adsorption material can be carried out by placing magnetic nanoparticles Fe3O4@SiO2, 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid in a 1,4-dioxane solvent, heating the mixed solution to react at 90±5°C, and washing and drying the product after magnetic separation to obtain the magnetic adsorption material Fe3O4@SiO2@BTT-Py.
[0014] The magnetic adsorption material Fe3O4@SiO2@BTT-Py was constructed by encapsulating magnetic Fe3O4 nanoparticles, which was used to enrich and extract benzimidazole drugs (BZDs) in water. It can stably adsorb the target compounds, achieve efficient enrichment and extraction of benzimidazole drugs, and improve the existing detection level. In addition, the good magnetic properties make it easier to separate. The adsorption of BZDs by Fe3O4@SiO2@BTT-Py on the molecular structure mainly includes the π-π conjugation between Fe3O4@SiO2@BTT-Py and BZDs, the p-π conjugation formed by the lone pair of electrons contained in -NH- on Fe3O4@SiO2@BTT-Py and the aromatic ring of BZDs, and the intermolecular hydrogen bonds formed between the strongly electronegative sulfur atoms contained in Fe3O4@SiO2@BTT-Py and BZDs. The cooperation of multiple forces significantly improves the enrichment and extraction rate of BZDs, thereby improving the existing detection level.
[0015] In the formation reaction of the core-shell structure, the porous material BTT-Py generated by the reaction of 1,3,5-benzenetrithiol, pyrrole and polyformaldehyde at a temperature of 85-95°C uniformly wraps Fe3O4@SiO2 to construct the magnetic adsorption material Fe3O4@SiO2@BTT-Py. The conjugated benzene rings and abundant sulfur and nitrogen atoms in the material can form strong adsorption effects such as intermolecular hydrogen bonds and π-π conjugation with benzimidazole drugs, which is beneficial to the efficient enrichment and extraction of benzimidazole drugs. The magnetic effect facilitates separation and subsequent desorption, thereby realizing the separation and qualitative / quantitative analysis of benzimidazole drugs in water.
[0016] As a limitation of the above technical solution, the magnetic adsorption material can simultaneously enrich and extract 19 benzimidazole drugs.
[0017] The adsorption material of the present invention can simultaneously extract a variety of benzimidazole drugs in water, and has the significant advantages of simultaneously extracting a variety of benzimidazole drugs and having a high enrichment and extraction rate.
[0018] At the same time, the present invention also provides a method for preparing the adsorption material for enrichment and extraction of benzimidazole drugs as described above, comprising the following steps:
[0019] 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid are placed in a solvent 1,4-dioxane, and the mixed solution is heated at 90±5°C for 22-30 hours. The product is separated, washed and dried to obtain an adsorption resin BTT-Py; the dosage ratio of the 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid is 1mmol:2-3mmol:5-6mmol:150-200μL; or
[0020] Fe3O4@SiO2 particles, 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid are placed in a 1,4-dioxane solvent, and the mixed solution is heated at 90±5°C for 22-30 hours. The product is washed and dried after magnetic separation to obtain a magnetic adsorption material Fe3O4@SiO2@BTT-Py; the dosage ratio of the Fe3O4@SiO2 particles, 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid is 130-180 mg: 1 mmol: 2-3 mmol: 5-6 mmol: 150-200 μL;
[0021] Preferably, methanol is used for washing after product separation;
[0022] Preferably, the product is washed and then dried under vacuum at 60-70° C. for 1-3 h.
[0023] The synthesis reaction of the adsorption material of the present invention does not need to be carried out in a vacuum environment, and the operation is simple and convenient. The prepared porous material has a stable structure, strong adsorption, and high enrichment and extraction efficiency, which is conducive to the promotion and application of the adsorption material.
[0024] As a limitation of the above technical solution, the method for preparing the adsorption material for enrichment and extraction of benzimidazole drugs comprises the following steps:
[0025] (1) Obtain spherical magnetic Fe3O4 nanoparticles, wash them, and vacuum dry them for later use;
[0026] (2) Coating SiO2 on the surface of magnetic Fe3O4 nanoparticles to obtain Fe3O4@SiO2 particles;
[0027] (3) Add Fe3O4@SiO2 particles to a round-bottom flask filled with 1,4-dioxane, and disperse Fe3O4@SiO2 uniformly by ultrasound. Then, add 1,3,5-benzenetrithiol and then add paraformaldehyde under constant stirring, and then add pyrrole dropwise. Finally, add hydrochloric acid dropwise to the round-bottom flask. Heat the mixture at 90±5°C for reaction. After magnetic separation, wash and dry the product to obtain the magnetic adsorption material Fe3O4@SiO2@BTT-Py.
[0028] As a preference,
[0029] Step (1) prepares spherical magnetic Fe3O4 nanoparticles by a solvothermal method, specifically comprising the following steps: dissolving FeCl3·6H2O in ethylene glycol, adding PEG-4000 and CH3COONa·3H2O, stirring and mixing, reacting at 200±5°C for 7-9h, washing the product with anhydrous ethanol, and vacuum drying at 60-70°C to obtain spherical magnetic Fe3O4 nanoparticles for standby use; the mass ratio of FeCl3·6H2O, PEG-4000 and CH3COONa·3H2O is 1.6:(1.8-2.4):(7.0-7.4); and / or
[0030] Step (2) uses tetraethyl orthosilicate hydrolysis method to coat SiO2 on the surface of magnetic Fe3O4 nanoparticles, which specifically includes the following steps: adding magnetic Fe3O4 nanoparticles to ethanol solution, ultrasonically dispersing them evenly, then adding ammonia water and tetraethyl orthosilicate, and obtaining Fe3O4@SiO2 particles through hydrolysis reaction; the amount ratio of the magnetic Fe3O4 nanoparticles, ethanol solution, ammonia water and tetraethyl orthosilicate is 0.1g:(90-110)mL:(1.2-1.7)mL:(0.8-1.2)mL; the volume ratio of anhydrous ethanol to water in the ethanol solution is (3-6):1; the hydrolysis reaction conditions are heating and stirring at 25-32°C for 20-26h.
[0031] Further improve the preparation conditions to obtain adsorption materials with stable structure and significant advantages in enrichment and extraction effects.
[0032] Furthermore, the present invention also provides a method for using the adsorption material for enrichment and extraction of benzimidazole drugs as described above, which is to use the adsorption material as an adsorbent for enrichment and extraction of benzimidazole drugs in water.
[0033] As a limitation of the above technical solution, the method of use specifically includes the following steps:
[0034] The adsorption resin prepared from the porous material BTT-Py is dry packed to obtain a solid phase extraction column, a water sample with a pH of 7 to 9 containing benzimidazole drugs is passed through the solid phase extraction column, and then eluted with an eluent, and the analyte is obtained after nitrogen blowing, redissolution, and filtration, and qualitative and / or quantitative determination is performed; or
[0035] A magnetic adsorption material made of a porous material BTT-Py is added to a water sample with a pH of 7 to 9 containing benzimidazole drugs, and after sufficient mixing and extraction, an external magnetic field is used to precipitate the magnetic adsorption material, and the supernatant is removed under the action of the magnetic field. Finally, an eluent is added to the collected magnetic adsorption material to recover the analyte, and qualitative and / or quantitative determination is performed;
[0036] Preferably, the eluent is methanol.
[0037] The sample obtained after enriching and extracting benzimidazole drugs in water using the adsorption material of the present invention as an adsorbent can be used for a variety of qualitative or quantitative analysis and detection methods, such as ultraviolet detection (UV), fluorescence detection (FLD) and liquid chromatography tandem mass spectrometry (LC-MS / MS) which are currently commonly used to analyze and detect benzimidazole drug residues, and is particularly suitable for the LC-MS / MS method which has the characteristics of good selectivity, high accuracy and low detection limit, and is used for the simultaneous detection of a variety of benzimidazole drugs in water samples.
[0038] The magnetic adsorption material of the present invention is used for enrichment and extraction of benzimidazole drugs in water, and has the advantages of convenient operation. The adsorption material has strong magnetism and stable structure. After mixed extraction, separation and recovery under the action of a magnetic field, and then elution, it can be used for subsequent conventional detection methods. It has strong and stable adsorption of target compounds and a high enrichment and extraction rate. The subsequent desorption is easy to operate and has a high desorption rate. It can achieve efficient recovery of 19 benzimidazole drugs at the same time, and the recovery rate is between 72.46 and 108.50%, indicating that the method is accurate and reliable. In the enrichment and extraction process, the adsorption and extraction time generally only takes 5 to 15 minutes, and the elution time generally only takes 7 to 11 minutes, and a sample for subsequent detection can be obtained. The operation is fast and convenient, and it is conducive to the rapid separation and analysis of multiple benzimidazole drugs in water samples. The adsorption material of the present invention also has the advantage of good reusability, which is conducive to efficient and practical detection.
[0039] In summary, the adsorption material of the present invention has significant advantages such as large specific surface area, high adsorption efficiency, and simultaneous extraction of multiple types of benzimidazole drugs, achieving the purpose of rapid separation and enrichment of benzimidazole drugs from water samples; and the preparation process of the material is simple, the structure is stable and can be reused many times, which can meet the needs of rapid separation and analysis of multiple benzimidazole drugs, and is of great significance for improving detection capabilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a flow chart for the preparation of the magnetic adsorption material Fe3O4@SiO2@BTT-Py of the present invention.
[0041] Figure 2 Scanning electron microscope images of Fe3O4 nanoparticles (A) and Fe3O4@SiO2@BTT-Py (B) in Example 1; Transmission electron microscope images of Fe3O4 nanoparticles (C) and Fe3O4@SiO2@BTT-Py (D).
[0042] Figure 3 This is the N2 adsorption-desorption characterization diagram of Fe3O4@SiO2@BTT-Py in Example 1.
[0043] Figure 4 This is a characterization diagram of the magnetic properties of Fe3O4 and Fe3O4@SiO2@BTT-Py in Example 1.
[0044] Figure 5 This is a diagram showing the adsorption effect of Fe3O4@SiO2@BTT-Py in Example 1 on the three-time recovery and reuse of 19 benzimidazole drugs in water samples. DETAILED DESCRIPTION
[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] The chemical raw materials involved in the following examples and comparative examples are all typical products purchased from the market, wherein ammonia water is purchased at a mass fraction of 25%, methanol is chromatographically pure, and other chemical raw materials are all analytically pure.
[0047] The preparation process of the magnetic adsorption material Fe3O4@SiO2@BTT-Py of the present invention is as follows Figure 1 shown.
[0048] Example 1
[0049] The magnetic adsorption material Fe3O4@SiO2@BTT-Py of this embodiment is specifically prepared as follows.
[0050] (1) Preparation of magnetic Fe3O4 nanoparticles: 1.6 g FeCl3·6H2O was accurately weighed and added to 60 mL ethylene glycol (the amount of ethylene glycol can be adjusted in the range of 60-65 mL). After stirring and dissolving with a magnetic stirrer, 2.0 g PEG-4000 and 7.2 g CH3COONa·3H2O were added respectively. Stirring was continued for 30 min to obtain a brown turbid solution, which was transferred to a reactor and reacted at 200°C for 8 h. The product was washed with anhydrous ethanol to obtain Fe3O4 nanoparticles, which were then dried in a vacuum at 60°C for 4 h.
[0051] (2) Preparation of Fe3O4@SiO2: 0.1 g of the Fe3O4 nanoparticles prepared in step (1) was added to 100 mL of ethanol solution, and the mixture was dispersed by ultrasonic for 30 min. Then, 1.5 mL of aqueous ammonia and 1.0 mL of tetraethyl orthosilicate were added to carry out hydrolysis reaction to obtain Fe3O4@SiO2 particles. The volume ratio of anhydrous ethanol to water in the ethanol solution was 4:1, and the hydrolysis reaction conditions were heating and stirring at 30°C for 24 h.
[0052] (3) Preparation of magnetic adsorption material Fe3O4@SiO2@BTT-Py: First, 150 mg of magnetic Fe3O4@SiO2 nanoparticles were added to a round-bottom flask containing 20 mL of 1,4-dioxane (the amount of 1,4-dioxane can be adjusted in the range of 20 to 25 mL). After ultrasonication for 5 min to uniformly disperse the Fe3O4@SiO2, 174 mg of 1,3,5-benzenetrithiol (1 mmol) was added under continuous stirring, followed by 180 mg of paraformaldehyde (6 mmol), and then 200 mg of pyrrole (3 mmol) was added dropwise. Finally, 200 μL of hydrochloric acid (mass concentration of 32%) was added dropwise to the round-bottom flask. The reaction mixture was heated to 90°C for 24 h. The obtained product was magnetically separated and washed with methanol until the supernatant became clear. It was then dried at 60°C in a vacuum oven for 2 h to obtain Fe3O4@SiO2@BTT-Py, which was a black powder. The obtained materials were characterized and the results were as follows Figure 2 to Figure 4 shown.
[0053] Figure 2These are scanning electron microscope (SEM) and transmission electron microscope (TEM) images of magnetic Fe3O4 nanoparticles and magnetic adsorption material Fe3O4@SiO2@BTT-Py, where A is the scanning electron microscope image of Fe3O4 nanoparticles, B is the scanning electron microscope image of Fe3O4@SiO2@BTT-Py, C is the transmission electron microscope image of Fe3O4 nanoparticles, and D is the transmission electron microscope image of Fe3O4@SiO2@BTT-Py. From the SEM images of the two materials, it can be seen that the magnetic Fe3O4 nanoparticles are spherical in structure. Since the nano Fe3O4 particles are easy to agglomerate, the surface is first coated with SiO2 to improve the dispersion of Fe3O4 and the uniformity of the coated shell material BTT-Py. The roughness of the coated Fe3O4@SiO2@BTT-Py particles is significantly increased, and there is obvious aggregation between the particles, which further proves that the BTT-Py generated by the reaction of 1,3,5-benzenetrithiol, pyrrole and polyformaldehyde under the catalysis of hydrochloric acid is successfully coated on the Fe3O4 nanoparticles. From the TEM images of the two nanoparticles, it can be seen that the Fe3O4 nanoparticles are basically uniform in shape, and it can be seen that the magnetic Fe3O4@SiO2@BTT-Py material has a clear core-shell structure, the inner core is composed of Fe3O4 nanoparticles, and the outer shell is composed of the porous material BTT-Py.
[0054] Figure 3 This is the nitrogen adsorption-desorption curve of the magnetic adsorption material Fe3O4@SiO2@BTT-Py at 77K. Through analysis and calculation, the specific surface area of the material is 38.18m 2 / g, with an average pore size of 6.54nm, a large specific surface area and a unique pore structure, which provide a guarantee for its excellent adsorption performance.
[0055] Figure 4 The hysteresis curves of magnetic Fe3O4 nanoparticles and magnetic adsorption material Fe3O4@SiO2@BTT-Py show that the saturation magnetization of Fe3O4 is 82.94emu / g, while that of Fe3O4@SiO2@BTT-Py is 9.47emu / g. Compared with Fe3O4, the magnetism of Fe3O4@SiO2@BTT-Py is significantly reduced, but it still has superparamagnetism and can still achieve rapid separation under the action of an external magnetic field.
[0056] The magnetic adsorption material Fe3O4@SiO2@BTT-Py synthesized in this embodiment is used as an adsorbent to extract benzimidazole drugs in water samples.
[0057] Weigh 12 mg of Fe3O4@SiO2@BTT-Py and add it to 10 mL of water sample (if the water sample is turbid, it can be filtered through a 0.45 μm nylon filter membrane or other methods, the same below) with a pH of 8 and containing 19 benzimidazole drugs (see Table 1-1 below, the concentration of each drug is 4 ng / mL). Vortex and oscillate for 10 min. Use an external magnetic field to precipitate Fe3O4@SiO2@BTT-Py. Remove the supernatant under the action of the magnetic field and add the collected Fe3O4@SiO2@BTT-Py to the water sample. 8 mL of methanol was added to 4@SiO2@BTT-Py, and the mixture was vortexed for 9 min. After the Fe3O4@SiO2@BTT-Py was precipitated by an external magnetic field, 4 mL of the eluent was blown to dryness with nitrogen, and re-dissolved with 1 mL of a mixed solution of methanol-0.1% formic acid water (0.1% is the volume ratio of formic acid in formic acid water, the same below) (the volume ratio of methanol to 0.1% formic acid water is 7:3, the same below), filtered through a 0.2 μm filter membrane, and injected into LC-MS / MS for analysis. The enrichment effect of Fe3O4@SiO2@BTT-Py on 19 benzimidazole drugs was evaluated by calculating the recovery rate, and the results are shown in Table 1-1.
[0058]
[0059] It can be seen from the results in the above table that the magnetic adsorption material of Example 1 simultaneously enriches and extracts 19 kinds of benzimidazole drugs in water, and the recovery rate is between 72.46% and 108.50% (the calculation of the recovery rate is based on the provisions of the recovery rate experiment in the national standard GB / T 27404-2008 "Quality Control Specification for Physical and Chemical Testing of Food in Experiments", which states that when the content of the measured component is less than 0.1 mg / kg, the reference range of the recovery rate is 60% to 120%), and can show a high recovery rate for a wide range of benzimidazole drugs, and can widely cope with various complex situations of residual benzimidazole drugs in environmental water samples and produce accurate detection results.
[0060] In addition, the magnetic adsorption material prepared in Example 1 was used to conduct enrichment and extraction tests on sulfonamides and β-lactam drugs (each drug concentration was 4 ng / mL) in water samples. The results are shown in Table 1-2.
[0061]
[0062] It can be seen from the data in Tables 1-2 above that the magnetic adsorption material of the present invention has a good enrichment and extraction effect only for benzimidazole drugs, but has a poor enrichment and extraction effect for other types of drugs.
[0063] According to the JC / T2021-2010 mesoporous material adsorption capacity test method, the adsorption capacity of the magnetic adsorption material of the present invention for 19 benzimidazole drugs is determined to be 1375 μg / g. Based on the measurement process, the adsorption capacity of a mixture of 19 benzimidazole drugs is measured using a magnetic adsorption material. The molecular weights of different benzimidazole drug molecules are different, resulting in the adsorption capacity results not being outstanding, but can meet practical requirements.
[0064] Example 2
[0065] The magnetic adsorption material Fe3O4@SiO2@BTT-Py of this embodiment is specifically prepared as follows.
[0066] (1) Preparation of magnetic Fe3O4 nanoparticles: 1.6 g FeCl3·6H2O was accurately weighed and added to 60 mL ethylene glycol. After dissolving with a magnetic stirrer, 1.9 g PEG-4000 and 7.1 g CH3COONa·3H2O were added respectively. Stirring was continued for 30 min to obtain a brown turbid solution. The solution was transferred to a reactor and reacted at 200°C for 7 h. The product was washed with anhydrous ethanol to obtain Fe3O4 nanoparticles, which were then dried in a vacuum oven at 60°C for 3 h.
[0067] (2) Preparation of Fe3O4@SiO2: 0.1 g of Fe3O4 nanoparticles prepared in step (1) was added to 110 mL of ethanol solution, and ultrasonic dispersion was performed for 30 min. Then, 1.3 mL of ammonia water and 0.9 mL of tetraethyl orthosilicate were added to perform hydrolysis reaction to obtain Fe3O4@SiO2 particles. The volume ratio of anhydrous ethanol to water in the ethanol solution was 3:1. The hydrolysis reaction conditions were heating and stirring at 25°C for 26 h.
[0068] (3) Preparation of magnetic adsorption material Fe3O4@SiO2@BTT-Py: First, 130 mg of Fe3O4@SiO2 particles were added to a round-bottom flask containing 20 mL of 1,4-dioxane, and the Fe3O4@SiO2 was evenly dispersed by ultrasonication for 5 min. Then, 174 mg of 1,3,5-benzenetrithiol (1 mmol) was added under continuous stirring, followed by 165 mg of paraformaldehyde (5.5 mmol), followed by dropwise addition of 160 mg of pyrrole (2.4 mmol), and finally 180 μL of hydrochloric acid (mass concentration of 32%) was added dropwise to the round-bottom flask. The reaction mixture was heated to 90°C for 26 h. The obtained product was magnetically separated and washed with methanol until the supernatant became clear, and then dried under vacuum at 60°C for 2 h to obtain Fe3O4@SiO2@BTT-Py. The microscopic characterization results of the obtained material showed that it was similar to the material obtained in Example 1.
[0069] The Fe3O4@SiO2@BTT-Py synthesized in this example was used as an adsorbent to extract benzimidazole drugs from water samples.
[0070] 12 mg of Fe3O4@SiO2@BTT-Py was weighed and added to 10 mL of water sample with a pH of 7 and containing 19 benzimidazole drugs (see Table 2 below, the concentration of each drug was 4 ng / mL). The solution was vortexed for 15 min and an external magnetic field was used to precipitate the Fe3O4@SiO2@BTT-Py. The supernatant was removed under the action of the magnetic field, and 8 mL of methanol was added to the collected Fe3O4@SiO2@BTT-Py. The solution was vortexed for 11 min and an external magnetic field was used to precipitate the Fe3O4@SiO2@BTT-Py. 4 mL of the eluent was blown dry with nitrogen and re-dissolved with 1 mL of a mixed solution of methanol-0.1% formic acid water (7:3, v:v). The solution was filtered through a 0.2 μm filter membrane and injected into LC-MS / MS for analysis. The enrichment effect of Fe3O4@SiO2@BTT-Py on 19 benzimidazole drugs was evaluated by calculating the recovery rate. The specific recovery rates are shown in Table 2.
[0071]
[0072]
[0073] It can be seen from the results in the above table that the magnetic adsorption material of Example 2 simultaneously enriches and extracts 19 benzimidazole drugs in water, with a recovery rate between 70.39% and 103.94%, and the enrichment and extraction rate is stable and excellent.
[0074] Example 3
[0075] The specific operation of the magnetic adsorption material Fe3O4@SiO2@BTT-Py in this embodiment is as follows.
[0076] (1) Preparation of magnetic Fe3O4 nanoparticles: 1.6 g FeCl3·6H2O was accurately weighed and dissolved in 60 mL ethylene glycol. After dissolving with a magnetic stirrer, 2.4 g PEG-4000 and 7.4 g CH3COONa·3H2O were added respectively. Stirring was continued for 30 min to obtain a brown turbid solution. The solution was transferred to a reactor and reacted at 200°C for 9 h. The product was washed with anhydrous ethanol to obtain Fe3O4 nanoparticles, which were then dried in a vacuum oven at 60°C for 2 h.
[0077] (2) Preparation of Fe3O4@SiO2: 0.1 g of Fe3O4 nanoparticles prepared in step (1) was added to 90 mL of ethanol solution, and ultrasonic dispersion was performed for 30 min. Then, 1.7 mL of ammonia water and 1.2 mL of tetraethyl orthosilicate were added to perform hydrolysis reaction to obtain Fe3O4@SiO2 particles. The volume ratio of anhydrous ethanol to water in the ethanol solution was 5:1. The hydrolysis reaction conditions were heating and stirring at 32°C for 20 h.
[0078] (3) Preparation of magnetic adsorption material Fe3O4@SiO2@BTT-Py: First, 180 mg of Fe3O4@SiO2 particles were added to a round-bottom flask containing 20 mL of 1,4-dioxane, and the Fe3O4@SiO2 was evenly dispersed by ultrasonication for 5 min. Then, 174 mg of 1,3,5-benzenetrithiol (1 mmol) was added under continuous stirring, followed by 150 mg of paraformaldehyde (5 mmol), followed by dropwise addition of 140 mg of pyrrole (2.1 mmol), and finally 160 μL of hydrochloric acid (mass concentration of 32%) was added dropwise to the round-bottom flask. The reaction mixture was heated to 90°C for 24 h. The obtained product was magnetically separated and washed with methanol until the supernatant became clear, and then dried under vacuum at 60°C for 2 h to obtain Fe3O4@SiO2@BTT-Py. The microscopic characterization results of the obtained material showed that it was similar to the material obtained in Example 1.
[0079] The Fe3O4@SiO2@BTT-Py synthesized in this example was used as an adsorbent to extract benzimidazole drugs from water samples.
[0080] 12 mg of Fe3O4@SiO2@BTT-Py was weighed and added to 10 mL of water sample with a pH of 9 and containing 19 benzimidazole drugs (see Table 3 below, the concentration of each drug was 4 ng / mL), vortexed for 5 min, and Fe3O4@SiO2@BTT-Py was precipitated using an external magnetic field. The supernatant was removed under the action of the magnetic field, and 8 mL of methanol was added to the collected Fe3O4@SiO2@BTT-Py. The mixture was vortexed for 7 min, and Fe3O4@SiO2@BTT-Py was precipitated using an external magnetic field. 4 mL of the eluent was blown to dryness with nitrogen, and re-dissolved with 1 mL of a mixed solution of methanol-0.1% formic acid water (7:3, v:v), filtered through a 0.2 μm filter membrane, and injected into LC-MS / MS for analysis. The enrichment effect of Fe3O4@SiO2@BTT-Py on 19 benzimidazole drugs was evaluated by calculating the recovery rate, and the recovery rate was 70.08-105.26%. The specific test results are shown in Table 3.
[0081]
[0082]
[0083] Example 4
[0084] The reusability of the magnetic adsorption material Fe3O4@SiO2@BTT-Py of Example 1 was tested. 19 benzimidazole drugs in water samples were enriched and extracted by Fe3O4@SiO2@BTT-Py and then recovered and reused. The specific application method is as follows:
[0085] 12 mg of the magnetic adsorption material Fe3O4@SiO2@BTT-Py of Example 1 was weighed and added to 10 mL of water sample with a pH of 8 and containing 19 benzimidazole drugs (each drug concentration was 4 ng / mL), vortexed for 5 min, and Fe3O4@SiO2@BTT-Py was precipitated using an external magnetic field, and the supernatant was removed under the action of the magnetic field. 8 mL of methanol was added to Fe3O4@SiO2@BTT-Py for elution, vortexed for 9 min, and Fe3O4@SiO2@BTT-Py was precipitated using an external magnetic field, and 4 mL of the eluent was blown to dryness with nitrogen, and re-dissolved with 1 mL of a mixed solution of methanol-0.1% formic acid water (7:3, v:v), filtered through a 0.2 μm filter membrane, and then sampled and analyzed for 19 benzimidazole drugs. Fe3O4@SiO2@BTT-Py was recovered, washed and dried with methanol, and then used in the adsorption experiment again according to the above steps, and the recovery rate was calculated.
[0086] The results are as follows Figure 5 As shown, the enrichment and extraction efficiency of the magnetic adsorption material Fe3O4@SiO2@BTT-Py of the present invention for benzimidazole drugs in water samples slowly decreases with the increase of the number of repeated uses. After three repeated uses, the recovery rate of 19 benzimidazole drugs is still between 65% and 82%, which is more than 72% of the initial use, indicating that the adsorption material has good stability and reusability.
[0087] Example 5
[0088] The adsorption material of this embodiment is adsorption resin BTT-Py, which is specifically prepared as follows.
[0089] (1) Preparation of adsorption resin BTT-Py: 174 mg 1,3,5-benzenetrithiol (1 mmol), 200 mg pyrrole (3 mmol), 80 mg paraformaldehyde (6 mmol) and 200 μL hydrochloric acid (mass concentration of 32%) were added to a round-bottom flask containing 20 mL 1,4-dioxane solvent, and the reaction mixture was heated to 90°C for 24 h. The obtained product was separated from the solid and liquid, washed with methanol until the supernatant became clear, and dried under vacuum at 60°C for 2 h to obtain BTT-Py, which was then ground into powder in an agate mortar for later use.
[0090] (2) Preparation of solid phase extraction column (taking experimental small column as an example, also called SPE column): Place a polypropylene sieve plate at the bottom of a 3 mL column tube, add 20 mg of BTT-Py into the empty column tube, place another sieve plate on top of the material, and gently press it with an iron rod to fix the position of the adsorbent.
[0091] The BTT-Py solid phase extraction column synthesized in this example was used to extract benzimidazole drugs in water samples.
[0092] The solid phase extraction column was activated with methanol and ultrapure water in turn, and then 50 mL of water sample with a pH of 8 and containing 19 benzimidazole drugs (see Table 4 below, the concentration of each drug is 4 ng / mL) was passed through the solid phase extraction column. After the sample solution was loaded, 3 mL of ultrapure water was added to the column tube to rinse the SPE column to remove potential interfering impurities on the SPE column. Then 8 mL of methanol was used to elute the target benzimidazole drugs retained on the adsorption resin BTT-Py and collected in a 15 mL centrifuge tube, 4 mL of the eluent was blown to dryness with nitrogen, and 1 mL of a mixed solution of methanol-0.1% formic acid water was used to dissolve, and after filtering through a 0.2 μm filter membrane, it was injected into LC-MS / MS for analysis. The enrichment effect of BTT-Py on 19 benzimidazole drugs was evaluated by calculating the recovery rate, and the results are shown in Table 4.
[0093]
[0094] Comparative Example 1
[0095] This comparative example is a material for enriching and extracting benzimidazole drugs. It is a carbon-nitrogen double bond material prepared by using Fe3O4@SiO2, 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine and 5-bromoisophthalaldehyde as raw materials, ethanol and 1,4-dioxane as solvents, and acetic acid as a catalyst. The specific preparation is as follows:
[0096] (1) 1.6 g of FeCl3·6H2O was dissolved in 60 mL of ethylene glycol, and then 2.0 g of PEG-4000 and 7.2 g of CH3COONa·3H2O were added and stirred thoroughly, and then reacted at 200°C for 8 h. The product was washed with anhydrous ethanol and then vacuum dried at 60°C to obtain spherical magnetic Fe3O4 nanoparticles for use;
[0097] (2) 200 mg of magnetic Fe3O4 nanoparticles were added to 200 mL of ethanol solution (the amount of anhydrous ethanol and water was 160 mL and 40 mL, respectively), and after ultrasonic dispersion, 3 mL of ammonia water and 2 mL of tetraethyl orthosilicate were added to obtain Fe3O4@SiO2 particles through hydrolysis reaction;
[0098] (3) 100 mg of Fe3O4@SiO2 was weighed and added to a round-bottom flask containing a mixed solvent of 15 mL of 1,4-dioxane and 30 mL of anhydrous ethanol. The mixture was ultrasonicated for 5 min. 5-Bromoisophthalaldehyde (0.18 g) and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine (0.21 g) were added under stirring. 1 mL of glacial acetic acid was slowly added dropwise. After reacting for 2 h, 1 mL of glacial acetic acid was added dropwise. The mixture was then heated at 70 °C for 24 h. The product was separated by magnetic separation and washed with ethanol until the supernatant became clear. The product was then dried under vacuum at 60 °C for 4 h.
[0099] The benzimidazole drugs were tested using the materials of Comparative Example 1 (the test experiment was the same as that of Example 1). The results are shown in Table 5 below.
[0100]
[0101]
[0102] As shown in Table 5, the material of Comparative Example 1 has a recovery rate of more than 63% for 15 benzimidazole drugs such as thiabendazole, but the recovery rates of mebendazole, fenbendazole, triclabendazole and triclabendazole are 50.23%, 59.15%, 51.25% and 57.62% respectively. In contrast, the material of Example 1 has a recovery rate of 72.46-108.50% for 19 benzimidazole drugs. This shows that the material of Example 1 has a good enrichment and extraction efficiency, is more suitable for extracting and detecting benzimidazole drugs, and provides a fast and accurate determination method for the supervision and monitoring of benzimidazole drugs in water.
[0103] The adsorption capacity of the magnetic adsorption material of Comparative Example 1 for 19 benzimidazole drugs was measured to be 1158 μg / g. Compared with Example 1, the magnetic adsorption material of the present invention further improved the adsorption capacity for 19 benzimidazole drugs.
[0104] Comparative Example 2
[0105] This comparative example involves the effect of changing the dosage ratio of the raw materials 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid in the preparation conditions of the magnetic adsorption material Fe3O4@SiO2@BTT-Py on the product. The specific preparation of the magnetic adsorption material is as follows.
[0106] (1) Preparation of magnetic Fe3O4 nanoparticles: 1.6 g FeCl3·6H2O was accurately weighed and dissolved in 60 mL ethylene glycol. After dissolving with a magnetic stirrer, 2.0 g PEG-4000 and 7.2 g CH3COONa·3H2O were added respectively. Stirring was continued for 30 min to obtain a brown turbid solution. The solution was transferred to a reactor and reacted at 200°C for 8 h. The product was washed with anhydrous ethanol to obtain Fe3O4 nanoparticles, which were then dried in a vacuum oven at 60°C for 4 h.
[0107] (2) Preparation of Fe3O4@SiO2: 0.1 g of the Fe3O4 nanoparticles prepared in step (1) was added to 100 mL of ethanol solution, and the mixture was dispersed by ultrasonic for 30 min. Then, 1.5 mL of aqueous ammonia and 1.0 mL of tetraethyl orthosilicate were added to carry out hydrolysis reaction to obtain Fe3O4@SiO2 particles. The volume ratio of anhydrous ethanol to water in the ethanol solution was 4:1, and the hydrolysis reaction conditions were heating and stirring at 30°C for 24 h.
[0108] (3) Preparation of magnetic adsorption material Fe3O4@SiO2@BTT-Py: First, 150 mg of Fe3O4@SiO2 particles were added to a round-bottom flask containing 20 mL of 1,4-dioxane. After ultrasonication for 5 min, 174 mg of 1,3,5-benzenetrithiol (1 mmol), 200 mg of pyrrole (3 mmol) and 210 mg of paraformaldehyde (7 mmol) were added in sequence. Finally, 100 μL of hydrochloric acid (mass concentration of 32%) was added to the round-bottom flask. The reaction mixture was heated to 90 °C and reacted for 24 h. The obtained product was mainly a black powdery solid, but with a few white particles. After magnetic separation, it was washed with methanol. During magnetic separation, some white particles flowed out with the detergent, but after multiple washings until the supernatant became clear, the white particles still existed. After drying, the small white particles and the black powdery solid can be further separated and vacuum dried at 60°C for 2h. The dried material is transferred to a dry filter paper and the obvious small white particles are removed. However, the above separation operation is complicated and easily leads to material loss and contamination. Therefore, the adsorption material prepared in Comparative Example 2 was not used to extract benzimidazole drugs in water samples.
[0109] According to the phenomenon of small white particles appearing in the synthesis of Comparative Example 2, it is judged that the polyformaldehyde is not completely reacted, which directly affects the properties of the adsorption material.
[0110] The selection of adsorbent materials requires comprehensive consideration of various factors such as the surface functional groups of the materials (such as whether the surface functional groups of the adsorbent materials can interact with the corresponding functional groups in the drug molecules through hydrogen bonds, electrostatic effects, etc.) and overall chemical stability, so as to achieve effective adsorption and separation of the drugs to be enriched. The adsorbent material of the present invention contains -NH- and sulfur atoms. Because -NH- contains lone pairs of electrons, it can form p-π conjugation with the aromatic ring of BZDs; the highly electronegative sulfur atoms can form intermolecular hydrogen bonds with BZDs, which is conducive to the conjugation and hydrogen bonding between the adsorbent material and the benzimidazole drugs, promotes adsorption, and can expand the range of adsorbed drugs and improve the enrichment and extraction rate, thereby significantly improving the detection level of drugs.
[0111] In summary, the present invention constructs an adsorption material with a porous material BTT-Py formed by the reaction of 1,3,5-benzenetrithiol, pyrrole and polyformaldehyde under the catalysis of hydrochloric acid, which is used to enrich and extract benzimidazole drugs in water. The -NH-, sulfur atom and benzene ring structure of the porous material BTT-Py are used to form multiple forces with the target compound, thereby achieving rapid separation and analysis of multiple benzimidazole drugs remaining in water samples, thereby improving the accuracy of drug residue detection.
Claims
1. An adsorption material for enrichment and extraction of benzimidazole drugs, characterized in that: The adsorption material comprises a porous material BTT-Py capable of enriching benzimidazole drugs, wherein the porous material BTT-Py is prepared by reacting 1,3,5-benzenetrithiol, pyrrole and polyformaldehyde under the catalysis of hydrochloric acid.
2. The adsorption material for enrichment and extraction of benzimidazole drugs according to claim 1, characterized in that: The porous material BTT-Py is prepared by placing 1,3,5-benzenetrithiol, pyrrole, paraformaldehyde and hydrochloric acid in a solvent 1,4-dioxane, and heating the mixed solution at 90±5° C. for reaction.
3. The adsorption material for enrichment and extraction of benzimidazole drugs according to claim 1, characterized in that: The adsorption material is adsorption resin or magnetic adsorption material.
4. The adsorption material for enrichment and extraction of benzimidazole drugs according to claim 3, characterized in that: The magnetic adsorption material has a core-shell structure, with magnetic Fe3O4 nanoparticles as the core and porous material BTT-Py as the shell.
5. The adsorption material for enrichment and extraction of benzimidazole drugs according to claim 4, characterized in that: The magnetic adsorption material is formed by firstly coating SiO2 on the surface of magnetic Fe3O4 nanoparticles to form Fe3O4@SiO2 particles, and then being coated by the porous material BTT-Py.
6. The adsorption material for enrichment and extraction of benzimidazole drugs according to claim 1, characterized in that: The adsorption material can simultaneously enrich and extract 19 benzimidazole drugs.
7. The method for preparing an adsorbent material for enriching and extracting benzimidazole drugs according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid are placed in a solvent 1,4-dioxane, and the mixed solution is heated at 90±5°C for 22-30 hours. The product is separated, washed and dried to obtain an adsorption resin BTT-Py; the dosage ratio of the 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid is 1mmol:2-3mmol:5-6mmol:150-200μL; or Fe3O4@SiO2 particles, 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid are placed in a 1,4-dioxane solvent, and the mixed solution is heated at 90±5°C for 22-30 hours. The product is washed and dried after magnetic separation to obtain a magnetic adsorption material Fe3O4@SiO2@BTT-Py; the dosage ratio of the Fe3O4@SiO2 particles, 1,3,5-benzenetrithiol, pyrrole, polyformaldehyde and hydrochloric acid is 130-180 mg: 1 mmol: 2-3 mmol: 5-6 mmol: 150-200 μL; Preferably, methanol is used for washing after product separation; Preferably, the product is washed and then dried under vacuum at 60-70° C. for 1-3 h.
8. The method for preparing an adsorbent material for enriching and extracting benzimidazole drugs according to claim 7, characterized in that: The preparation of the magnetic adsorption material comprises the following steps: (1) Obtain spherical magnetic Fe3O4 nanoparticles, wash them, and vacuum dry them for later use; (2) Coating SiO2 on the surface of magnetic Fe3O4 nanoparticles to obtain Fe3O4@SiO2 particles; (3) Add Fe3O4@SiO2 particles to a round-bottom flask filled with 1,4-dioxane, and disperse Fe3O4@SiO2 uniformly by ultrasound. Then, add 1,3,5-benzenetrithiol and then add paraformaldehyde under constant stirring, and then add pyrrole dropwise. Finally, add hydrochloric acid dropwise to the round-bottom flask. Heat the mixture at 90±5°C for reaction. After magnetic separation, wash and dry the product to obtain the magnetic adsorption material Fe3O4@SiO2@BTT-Py. As a preference, Step (1) prepares spherical magnetic Fe3O4 nanoparticles by a solvothermal method, specifically comprising the following steps: dissolving FeCl3·6H2O in ethylene glycol, adding PEG-4000 and CH3COONa·3H2O, stirring and mixing, reacting at 200±5°C for 7-9h, washing the product with anhydrous ethanol, and vacuum drying at 60-70°C to obtain spherical magnetic Fe3O4 nanoparticles for standby use; the mass ratio of FeCl3·6H2O, PEG-4000 and CH3COONa·3H2O is 1.6:(1.8-2.4):(7.0-7.4); and / or Step (2) uses tetraethyl orthosilicate hydrolysis method to coat SiO2 on the surface of magnetic Fe3O4 nanoparticles, which specifically includes the following steps: adding magnetic Fe3O4 nanoparticles to ethanol solution, ultrasonically dispersing them evenly, then adding ammonia water and tetraethyl orthosilicate, and obtaining Fe3O4@SiO2 particles through hydrolysis reaction; the amount ratio of the magnetic Fe3O4 nanoparticles, ethanol solution, ammonia water and tetraethyl orthosilicate is 0.1g:(90-110)mL:(1.2-1.7)mL:(0.8-1.2)mL; the volume ratio of anhydrous ethanol to water in the ethanol solution is (3-6):1; the hydrolysis reaction conditions are heating and stirring at 25-32°C for 20-26h.
9. The method for using the adsorption material for enrichment and extraction of benzimidazole drugs according to any one of claims 1 to 6, characterized in that: The adsorption material is used as an adsorbent to enrich and extract benzimidazole drugs in water.
10. The method for using the adsorption material for enrichment and extraction of benzimidazole drugs according to claim 9, characterized in that: The specific steps include: The adsorption resin prepared from the porous material BTT-Py is dry packed to obtain a solid phase extraction column, a water sample with a pH of 7 to 9 containing benzimidazole drugs is passed through the solid phase extraction column, and then eluted with an eluent, and the analyte is obtained after nitrogen blowing, redissolution, and filtration, and qualitative and / or quantitative determination is performed; or A magnetic adsorption material made of a porous material BTT-Py is added to a water sample with a pH of 7 to 9 containing benzimidazole drugs, and after sufficient mixing and extraction, an external magnetic field is used to precipitate the magnetic adsorption material, and the supernatant is removed under the action of the magnetic field. Finally, an eluent is added to the collected magnetic adsorption material to recover the analyte, and qualitative and / or quantitative determination is performed; Preferably, the eluent is methanol.